2018
DOI: 10.1007/s00464-018-06619-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic paraesophageal hernia repair in octogenarians: a registry-based, propensity score-matched comparison of 360 patients

Abstract: Background Paraesophageal hernias (PEH) tend to occur in elderly patients and the assumed higher morbidity of PEH repair may dissuade clinicians from seeking a surgical solution. On the other hand, the mortality rate for emergency repairs shows a sevenfold increase compared to elective repairs. This analysis evaluates the complication rates after elective PEH repair in patients 80 years and older in comparison with younger patients. Methods In total, 3209 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…“The Herniamed quality assurance study is a multicenter internet-based hernia registry with voluntary participating institutions which incorporate prospective data of patients who have undergone routine hernia surgery” [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…“The Herniamed quality assurance study is a multicenter internet-based hernia registry with voluntary participating institutions which incorporate prospective data of patients who have undergone routine hernia surgery” [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…“These data are obtained from 712 voluntarily participating hospitals and surgeons in Germany, Austria, and Switzerland” [ 20 , 21 ]. All patients gave informed consent agreeing to participate [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In other studies, propensity scoring and matched sampling techniques have been used to adjust for age and comorbidities, and have found that age alone did not correspond with increased complications or that nonelective repair was the primary risk factor. 16,17 Age may not be the true risk factor for PEHR, but rather acuity and comorbidities. Frailty may become a better-combined marker to predict complication risk as suggested by a study by Augustin et al, 8 and may warrant further study.…”
Section: Discussionmentioning
confidence: 99%